Editorial - Oxford, Rebecca L.; Pawlak, Mirosław (Studies in Second Language Learning and Teaching, 2018)
We welcome you to our special issue of Studies in Second Language Learning and Teaching (SSLLT). Our focus is language learning strategies, or LLS. We have been discussing the need for this special issue for years. Over coffee, sodas, or Chardonnet at many conferences and via emails and Skype, we discussed urgent issues in LLS assessment, research, and instruction. SSLLT, like many journals, has published numerous articles involving LLS, and other journals have had special issues on LLS. However, the time is ripe for a special issue that systematically includes LLS for all language skill areas, all major cross-cutting language subsystems such as grammar, and some important yet often ignored topics, such as strategies for learning culture and for technology-enhanced language learning (TELL), which greatly advances decades of research on computer-assisted language learning (CALL). We have gathered articles from a talented team of researchers, most of them well-known and the others rising stars. The articles in this special issue directly involve LLS research in several world regions and allude to such research in many more regions.